PENGARUH KOMPENSASI, PENDIDIKAN DAN PELATIHAN, LINGKUNGAN KERJA, DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus di PT XYZ Jakarta) - Rahmawati, Anisa (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to determine the simultaneous and partial effects of compensation, education and training, work environment, and work experience as well as knowing what the variable most dominant influence on employee productivity. This research is an explanatory research, which explain the causal relationship among the variables through the testing of hypotheses. This research is held in the office of PT XYZ Jakarta. The sample in this research is 90 respondents. The independent variables are Compensation (X1), Education and Training (X2), Working Environment (X3), and Work Experience (X4). While the dependent variable is the Employee Productivity (Y).Data have been analyzed further accurately by using Classic Assumption Test, Double Linear Regression and Analysis Hypotheses Test which supported with Coumputer SPSS Version 17 for windows programs.The results of this research is there is a simultaneous and partial effects between compensation, education and training, work environment, and work experience on employee productivity. This means that compensation, education and training, work environment, and work experience can significantly improve the employee productivity. The most dominant variable comes from the work environment variable.Keywords : Employee Productivity, Compensation, Education and Training, Work Environment, and Work Experience